Telecommunications Infrastructure and Economic Development: A Simultaneous Approach - Röller, Lars-Hendrik; Waverman, Leonard (American Economic Review, 2001)
In this paper we investigate how telecommunications infrastructure affects economic growth. We use evidence from 21 OECD countries over a 20-year period to examine the impacts that telecommunications developments may have had. We jointly estimate a micromodel for telecommunication investment with a macro production function. We find evidence of a significant positive causal link, especially when a critical mass of telecommunications infrastructure is present. Interestingly, the critical mass appears to be at a level of telecommunications infrastructure that is near universal service. (JEL O57, O47, L69)